Studi tentang Hadis Malam Nisfu Sya'ban - Andaryuni, Lilik (Mazahib, 2014)
The glory and privilege month of Sya`ban is because it is the month with full of intercession, forgiveness, and rewards. In this month, man should do a lot of self introspection, because this month is the closing month of Islamic calendar. Prophet Muhammad did a lot of fasting in the month of Sya`ban because he loved when his pious acts were accounted for in the fasting state. There are different opinions, however, when it comes to the status of the 15th night of Sya`ban: is it a special evening with a special virtue too or it is no more than the rest of Sya`ban nights? This article thus will analyze ulama’s opinions on this matter.